The Day the Universe Exploded my Head : Poems to Take you Into Space and Back Again - Wolf, Allan; Raff, Anna (Somerville, Massachusetts : Candlewick Press, 2019)
Creative nonfiction poetry combines humor, creative imagery, and illustrations to explain topics in astronomy and other space sciences.
Hang on tight for a raucous bounce through the solar system and back -- propelled by funny, fanciful, factually sound poems and exuberant illustrations. The universe poured into me. My brain was overloaded. It smoked and glowed red-hot. And then it actually exploded. Ever wonder what the sun has to say about being the closest star to Earth? Or what Pluto has gotten up to since being demoted to a dwarf planet? Or where rocket ships go when they retire? Listen closely, because maybe, just maybe, your head will explode, too. With poetry that is equal parts accurate and entertaining -- and illustrations that are positively out of this world -- this book will enthrall amateur stargazers and budding astrophysicists as it reveals many of the wonders our universe holds. Space travelers in search of more information will find notes about the poems, a glossary, and a list of resources at the end.
The Sun : a solar sunnet, er, sonnet -- The Sun did not go down today -- A Moon buffet -- Shooting stars : Perseid meteor shower (poem for three meteors) -- Meteorite : chaos in Chelyabinsk February 15, 2013 -- Mercury : given to extremes -- Venus (come live with me and be my lunch) -- Earth : your mother I'll be -- Mars : a Martian sonnet -- The Moons of Mars : fear and terror! (poem for two small moons) -- Jupiter : I'm Jupiter the giant -- Saturn : and the winner for best wardrobe is ... -- Uranus : the planet behind the blue-green mask -- Neptune : the lonesome, on-my-own-some Neptune blues -- The moons of Neptune : roses are red, Neptune is blue -- Planet X -- Pluto and Charon : dancing with the stars (poem for a dwarf planet and its moons) -- Twinkle, twinkle little man -- Going the distance : (rap for two voices) -- Solar eclipse : (poem for Dr. Jekyll and Mr. Hyde) -- Lunar eclipse : (poem for Dr. Jekyll and Mr. Hyde) -- Black hole -- A Sputnik moment : first artificial satellite October 4, 1957 (poem for two scientists) -- Ivan Ivanovich : mannequin cosmonaut March 1961 -- The children of astronomy -- For those who light the candle : for the astronauts and cosmonauts who have given their lives to travel into space -- The rocket launch -- The rusty rockets retirement garden : Kennedy Space Center, Merritt Island, Florida (poem for four aging rockets) -- The day the universe exploded my head : (poem for one human, one heart, and one brain) -- Notes on the poems -- Glossary of selected space terms -- Internet resources -- Acknowledgements.
Includes bibliographical references and glossary.
Keywords: Space sciences -- Juvenile poetry; Planets -- Juvenile poetry; Children's poetry, English; Planets -- Poetry; Science -- Poetry; Humorous poetry; Solar System Poetry; Outer Space Poetry; Technology - Aeronautics, Astronautics & Space Science; Science & Nature -- Astronomy; Children's poetry, English; Outer space -- Juvenile poetry; Outer space -- Poetry; Outer space; Children's poetry; Juvenile works; Poetry; Humorous poetry; Poetry